Upaya Peningkatan Hasil Belajar IPAS Melalui Model Problem Based Learning Terintegrasi TaRL pada Siswa Kelas IV SD Negeri Datar - Fita Endah Pratiwi; Afriatun Afriatun; Anggun Badu Kusuma (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
This research aims to improve student learning outcomes through the application of the Problem Based Learning (PBL) learning model integrated with the Teaching at The Right Level (TaRL) learning approach. This research was conducted at a partner school when implementing PPL II, namely SD Negeri Datar. This type of research is Classroom Action Research (PTK). Data collection methods use test techniques (evaluation questions), non-test techniques (teacher activity observation sheets and student activity observation sheets), and documentation. The type of research is quantitative. The research subjects were fourth grade students at Flat State Elementary School with a total of 31 students. The research results generally show an increase in students’ science and science learning outcomes, which can be seen from the average score in cycle I of 70.3 with a completion percentage of 54.8%. The science learning results in cycle II obtained an average of 80.09 with a completion percentage of 90.3% with very good criteria. The results of the research show that the application of the Problem Based Learning (PBL) learning model integrated with the Teaching at The Right Level (TaRL) learning approach is very effective to be used to improve science and science learning outcomes for class IV students at SD Negeri Datar in 2023/2024.